PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT Audio Sumitomo Technology (AST) Indonesia) - Fakhri, Risha Faiq; Djastuti, Indi (Diponegoro Journal of Management, 2015)
Compensation and training is directly related to the employee's performance. Compensation and training obtained by the employees can degrade performance or improve employee performance. Employees who receive compensation in accordance with what he hoped would directly improve the performance he had, as well as the training provided, in accordance with the job training will enhance the ability of the employee, so that the performance possessed will also increase.This research was conducted at PT. Audio Sumitomo Technology (AST) Indonesia. This study aims to determine the effect of training and compensation moderated by job satisfaction on employee performance. The number of samples is set as much as 79 respondents using purposive sampling method. As independent variables, namely compensation and training, and the moderating variable is job satisfaction, while the dependent variable is the performance of employees. The analysis includes the validity, reliability, classic assumption test, models test, hypothesis testing, path analysis, and Sobel test.From the analysis it can be seen that the variable compensation and training had positive effect on employee performance, and job satisfaction moderating variable compensation and training on employee performance. Results of analysis using the coefficient of determination is known that 99.8 percent of the employee's performance can be explained by the independent variable and the moderating variables were examined in this study and 0.2 percent is explained by other factors outside the model.